Dendritic Si growth morphologies in highly undercooled Al–Si alloys - Dongmei Liu; Yindong Fang; Stefan Nolte; Stephanie Lippmann (Journal of Materials Research and Technology, 2024)
The morphology of primarily crystallizing Si in hypereutectic Al-(20, 40, 55) wt%Si alloys during conventional casting (nucleation undercooling ΔT<1 K) and solidification at high undercoolings (ΔT up to 335 K) has been investigated. As expected, at higher undercoolings a higher nucleation frequency and fast growth of primary Si is observed, leading to the formation of multiple microstructural zones. Instead of the well-known plate-like Si in the as-cast microstructure, various morphologies of primary Si such as faceted and non-faceted blocky morphologies as well as dendrites with aligned side branches showing constant spacing features are observed after solidification at high undercoolings. The special Si dendrites only grow in a limited range of melt concentrations and undercoolings. The transition from faceted to non-faceted growth appears to occur in several steps, as Si dendrites with similar features of the secondary arms as in non-faceted metal alloys are also observed.